2017
DOI: 10.1371/journal.pone.0181196
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between socioeconomic disparity and functional outcome after acute ischemic stroke?

Abstract: BackgroundTo investigate the impact of low socioeconomic status (SES), indicated by low level of education, occupation and income, on 3 months functional outcome after ischemic stroke.MethodsWe analyzed data from the China National Stroke Registry (CNSR), a multicenter and prospective registry of consecutive patients with acute cerebrovascular events occurred between September 2007 and August 2008. 11226 patients with ischemic stroke had SES and clinical characteristics data collected at baseline and mRS measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 30 publications
0
39
0
6
Order By: Relevance
“…Low SES has been shown to influence morbidity and mortality of stroke worldwide (5), increase the incidence of stroke, and affect accessibility of evidence-based stroke care in both the acute and chronic stages of injury-even among countries with universal health care (5,10,11). Importantly, acute and longterm functional outcome following stroke appears to be linked to SES independent of stroke severity, risk factors, and access to acute stroke care (12)(13)(14). The specific aspects of low SES which affect stroke outcome remain to be clarified, but social isolation and social defeat stress may have an important influence on both stroke injury and stroke recovery.…”
Section: Socioeconomic Status Social Isolation and Social Defeat Stress: Consequences For Strokementioning
confidence: 99%
“…Low SES has been shown to influence morbidity and mortality of stroke worldwide (5), increase the incidence of stroke, and affect accessibility of evidence-based stroke care in both the acute and chronic stages of injury-even among countries with universal health care (5,10,11). Importantly, acute and longterm functional outcome following stroke appears to be linked to SES independent of stroke severity, risk factors, and access to acute stroke care (12)(13)(14). The specific aspects of low SES which affect stroke outcome remain to be clarified, but social isolation and social defeat stress may have an important influence on both stroke injury and stroke recovery.…”
Section: Socioeconomic Status Social Isolation and Social Defeat Stress: Consequences For Strokementioning
confidence: 99%
“…However, it is uncertain whether low socioeconomic status is associated with increased functional impairment after stroke. Some previous studies have indicated that low socioeconomic status is associated with functional impairment at 3 months after stroke (Chen et al, 2015;Song et al, 2017). Dysphagia is a common consequence of stroke and is a risk factor for aspiration pneumonia (Martino et al, 2005), which is associated with higher rates of death and disability (Cohen et al, 2016).…”
Section: Perspectives On Equal Health and Well-beingmentioning
confidence: 99%
“…Todavia os mesmos também constataram que após 3 meses do AVC a probabilidade de prognóstico com maior funcionalidade estava diretamente ligada aos maiores níveis educacionais, principalmente quando compararam pessoas com ensino fundamental incompleto e pessoas com nível superior. Contrapondo alguns achados deGrube et al (2012), o estudode Fernandes et al (2012) observou diferenças entre indivíduos com diferentes níveis de escolaridade ainda na fase aguda do AVC.Fernandes et al (2012) observaram um maior índice de incapacidade e algum tipo de perda na funcionalidade em pessoas que não completaram o ensino formal ao avaliar a participação nas atividades de vida diária dos indivíduos 6 meses após o AVC.Resultado semelhante achado porVan Den Bos et al (2002) em um estudo realizado para observar as consequências em longo prazo após, 3 e 5 anos, do episódio vascular.Reforçando os desfechos encontrados por Grube et al(2012) eFernandes (et al 2012), em um estudo realizado porBettger et al (2014) constatou-se que pacientes que não haviam completado o ensino formal tinham mais chances de ter alguma deficiência após 3 meses do AVE. Os autores ainda afirmam que essa variável socioeconômica interfere de forma independente dos outros indicadores.Em um estudo realizado porSong et al (2017), foram associadas outras características socioeconômicas além da escolaridade. PorémSong et al (2017), diferentemente deBettger et al (2014), encontraram que independentemente do nível escolar e tipo de ocupação, a baixa renda foi mais significativamente associada aos maiores níveis de dano funcional.…”
unclassified
“…PorémSong et al (2017), diferentemente deBettger et al (2014), encontraram que independentemente do nível escolar e tipo de ocupação, a baixa renda foi mais significativamente associada aos maiores níveis de dano funcional. Este não corrobora com os estudos que utilizam apenas a escolaridade como indicador de condição socioeconômica deGrube et al (2012),Fernandes et al (2012) eVan Den Bos et al (2002) Song et al (2017). ainda concluíram que a combinação entre baixa renda e trabalhos manuais/desemprego foi a que obteve achados mais estatisticamente significativos para piores desempenhos funcionais pós AVC, e que, quanto mais privações socioeconômicas, maior a associação com piores prognósticos funcionais.…”
unclassified
See 1 more Smart Citation